Pretrial Detainees, Sentenced Prisoners, and Treatment Motivation - Weinrath, Michael (International journal of offender therapy and comparative criminology, 2019)
A dilemma for corrections practitioners is treatment for pretrial detainees. They are innocent until proven guilty and are not required to take treatment, but many may benefit from intervention. To assess the general level of treatment interest and potential differences, a sample of 221 male remand and sentenced Canadian provincial prisoners completed several Client Evaluation of Self and Treatment (CEST) scales. Prisoner treatment motivation and its correlates were assessed by examining univariate, bivariate, and multivariate effects for demographic attributes, legal factors, risk, perceptions of personal/family/pressure for treatment, and depression. It was found that about 36% to 40% of study subjects expressed moderate to strong motivation for treatment. Age, pressure, and depression were the only correlates consistently associated with treatment motivation. There were no differences found between remand and sentenced prisoners. Results indicated that pretrial detainees have a definite interest in undertaking programming.